Shear strengthening of reinforced concrete beam using natural fibre reinforced polymer laminates - Alam M.A.; Al Riyami K. (Elsevier Ltd, 2023)
Beams and girders; Bridge decks; Carbon; Carbon fiber reinforced plastics; Carbon fibers; Concrete beams and girders; Concrete buildings; Concrete construction; Concretes; Construction industry; Ductility; Fiber reinforced plastics; Fibers; Fracture; Hemp; Laminated composites; Laminates; Natural fibers; Plates (structural components); Reinforced concrete; Reinforced plastics; Rope; Steel fibers; Strengthening (metal); Textile fibers; Carbon fibre reinforced polymer; Natural fibre composites; Natural fibre reinforced polymers; RC beams; Reinforced concrete beams; Shear strengthening; Strain characteristics; Structural behaviour; Tensile strength